2013
DOI: 10.1007/s12020-013-0093-x
|View full text |Cite
|
Sign up to set email alerts
|

Prolactinoma ErbB receptor expression and targeted therapy for aggressive tumors

Abstract: Purpose As ErbB signaling is a determinant of prolactin synthesis, role of ErbB receptors was tested for prolactinoma outcomes and therapy. The objective of this study was to characterize ErbB receptor expression in prolactinomas and then perform a pilot study treating resistant prolactinomas with a targeted tyrosine kinase inhibitor (TKI). Methods Retrospective analysis of prolactinomas and pilot study for dopamine agonist resistant prolactinomas in tertiary referral center. We performed immunofluorescent s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
56
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 56 publications
(51 reference statements)
1
56
0
3
Order By: Relevance
“…Identification of new molecular markers highly expressed or down-regulated in these giant tumours should help to better understand their origin and progression (27,120) and to find new therapeutic modalities, such as drugs interfering with angiogenesis or cell proliferation. An example of such strategy is the recent observation of specific expression of ErbB receptors in prolactinomas, which was associated with tumour invasion and response to DAs (121). Thus, targeting ErbB receptors might be a future effective therapy in patients with large aggressive prolactinomas.…”
Section: Perspectives In the Management Of Giant Prolactinomasmentioning
confidence: 99%
“…Identification of new molecular markers highly expressed or down-regulated in these giant tumours should help to better understand their origin and progression (27,120) and to find new therapeutic modalities, such as drugs interfering with angiogenesis or cell proliferation. An example of such strategy is the recent observation of specific expression of ErbB receptors in prolactinomas, which was associated with tumour invasion and response to DAs (121). Thus, targeting ErbB receptors might be a future effective therapy in patients with large aggressive prolactinomas.…”
Section: Perspectives In the Management Of Giant Prolactinomasmentioning
confidence: 99%
“…More aggressive pituitary adenomas show higher EGFR and ErbB2 protein expression, with 40% of invasive adenomas staining positive for ErbB2 compared to 1.2% of noninvasive adenomas [19]. We demonstrated that approximately 80% of 28 human prolactinomas express ErbB receptors [20**], with EGFR positivity in 23/28 (82%), ErbB2 positivity in 24/26 (92%), ErbB3 positivity in 7/28 (25%), and ErbB4 positivity in 20/28 (71%). Higher ErbB3 expression was correlated with higher rates of optic chiasm compression, suprasellar extension, and encasement of the carotids compared to those without these radiologic findings.…”
Section: Targeting the Erbb Pathway In Lactotroph Adenomasmentioning
confidence: 99%
“…Higher ErbB4 was observed in tumors with sphenoid sinus invasion compared to those without invasion. Two subjects who experienced tumor shrinkage and PRL reduction on dopamine agonist therapy had tumors which were 100% percent positive for ErbB3 on their adenomas compared to 13 without tumor reduction who had 0-10% ErbB3 staining [20**]. …”
Section: Targeting the Erbb Pathway In Lactotroph Adenomasmentioning
confidence: 99%
“…EGFR/HER2 signaling regulates tumor growth and hormone production in experimental lacto-somatotroph tumors and in an experimental Cushing disease model (24 -27). Moreover, targeted EGFR/HER2 therapy has also been shown to be effective in 2 dopamine agonist resistant prolactinomas (28).…”
mentioning
confidence: 99%